Descriptive Inorganic Chemistry Researches of Metal Compounds 2017
DOI: 10.5772/67584
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Complexes with Antipyrine‐Derived Schiff Bases: Synthesis and Antibacterial Activity

Abstract: The increase of death rate, associated with infectious diseases, is directly linked to the bacteria that have multiple resistance to antibiotics. The lack of efficient medical treatment is the main cause of this problem. The synthesis of new antibacterial agents, through various methods, is, for sure, an emergency medical issue. Recent research focuses more and more on the synthesis of complexes of the transitional metals with ligands of Schiff-base type, as a result of the biological properties which they hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Aeruginosa. Based on the results, they have reported that some of the compounds (10), among all, can be used as an alternative ti Streptomycin due to the resistance to it [41]. A review reported on the nature and applications of Schiff bases.…”
Section: Fig 32: New Schiff Bases Containing Nickel (Ni) Metalmentioning
confidence: 99%
“…Aeruginosa. Based on the results, they have reported that some of the compounds (10), among all, can be used as an alternative ti Streptomycin due to the resistance to it [41]. A review reported on the nature and applications of Schiff bases.…”
Section: Fig 32: New Schiff Bases Containing Nickel (Ni) Metalmentioning
confidence: 99%